2019
DOI: 10.21149/8886
|View full text |Cite
|
Sign up to set email alerts
|

Association of globalization in its different dimensions with overweight and obesity: an analysis in 10 Latin American and Caribbean countries

Abstract: García CM García CM. Association of globalization in its different dimensions with overweight and obesity: an analysis in 10 Latin American and Caribbean countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
8
0
4
Order By: Relevance
“…The annual GDP per capita in 2017 for the coast, the mountain and the jungle were 9,764, 3,780 and 2,442 US dollars [38]. The prevalence of AO in coastal cities may be higher because people with a high level of well-being, especially those in an urban environment, are more likely to engage in unhealthy routine behaviors such as sedentarism and consumption of high caloric food [39], in addition, these people are exposed to a great amount of advertising of caloric dense food [40]. Furthermore, the wealthiest individuals tend to suffer 'technological sedentarism' due to greater access to their own form of motorized transport and greater quantities of office work which promote less physical activity [41].…”
Section: Plos Onementioning
confidence: 99%
“…The annual GDP per capita in 2017 for the coast, the mountain and the jungle were 9,764, 3,780 and 2,442 US dollars [38]. The prevalence of AO in coastal cities may be higher because people with a high level of well-being, especially those in an urban environment, are more likely to engage in unhealthy routine behaviors such as sedentarism and consumption of high caloric food [39], in addition, these people are exposed to a great amount of advertising of caloric dense food [40]. Furthermore, the wealthiest individuals tend to suffer 'technological sedentarism' due to greater access to their own form of motorized transport and greater quantities of office work which promote less physical activity [41].…”
Section: Plos Onementioning
confidence: 99%
“…Therefore, this study investigated the interaction among obesity, educational attainment, and economic globalization in sample of the BRICS economies, the drivers of the global economy during the past a few decades. The influence of globalization and its main dimensions on obesity has been investigated by very few researchers in Table 2, and they have generally utilized regression analysis to find a positive influence of globalization on obesity (17,18,(32)(33)(34)(36)(37)(38). However, Ghosh (35) found that the influence of globalization on obesity changed depending on countries' income levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The obesity rate has tripled since 1975, resulting in over 39% of adults becoming overweight and 13% becoming obese (Connors et al , 2021). If this trend continues, it is estimated that by 2025, the global obesity rate for men will reach 18% and that for women will exceed 21% (García, 2019). Numerous factors contribute to obesity, which is a complex problem.…”
Section: Introductionmentioning
confidence: 99%